Pharmacy students’ experiences in provision of community pharmacy mental health services - Murphy, Andrea (SAGE Publications, 2014)
BACKGROUND: Little information is available describing the pharmacy student’s experience working in community practice with people with lived experience of mental illness. Students’ perspectives as observers, learners, technical staff and future pharmacists are important. OBJECTIVE: To gain a better understanding of the pharmacy student experience in community pharmacy–based service provision to people with lived experience of mental illness. METHODS: We conducted a qualitative study using interpretive description and application of the Theoretical Domains Framework. Focus groups were held with third- and fourth-year undergraduate pharmacy students from one Canadian university. RESULTS: Two student focus groups were held in the fall of 2012 with 11 students (7 third year and 4 fourth year), 6 women and 5 men, mean age 24.5 (range, 21 to 30) years, averaging 3.2 years (range, 2 weeks to 7 years) of cumulative, mostly part-time, community pharmacy experience. Three broad themes emerged from the pharmacy student experience: (1) business tension; (2) roles, responsibilities and relationships; and (3) stigma. Students discussed their own roles, responsibilities and relationships in a pluralistic identity experience (i.e., pharmacy student, technician, future pharmacist). Application of the Theoretical Domains Framework demonstrated numerous influences on behaviour. CONCLUSIONS: From the students’ description of community pharmacy–based care of people with lived experience of mental illness, significant issues exist with current practices and behaviours. Advancing the role of pharmacists and pharmacy students to meet the needs of people with mental illness will require strategies to address multifactorial influences on behaviour.